Collagenase Clostridium Histolyticum versus Limited Fasciectomy for Dupuytren's Contracture: Outcomes from a Multicenter Propensity Score Matched Study. Issue 1 (July 2015) - Zhou, Chao; Hovius, Steven E. R.; Slijper, Harm P.; Feitz, Reinier; Van Nieuwenhoven, Christianne A.; Pieters, Adriana J.; Selles, Ruud W.
Abstract : Background: Controversy exists about the relative effectiveness of injectable collagenase (collagenase clostridium histolyticum) and limited fasciectomy in the treatment of Dupuytren's contracture. The authors compared the effectiveness of both techniques in actual clinical practice. Methods: This study evaluated all subjects treated with collagenase clostridium histolyticum or limited fasciectomy for metacarpophalangeal and/or proximal interphalangeal joint contractures between 2011 and 2014 at seven practice sites. The authors compared the degree of residual contracture (active extension deficit), Michigan Hand Outcomes Questionnaire scores, and adverse events at follow-up visits occurring between 6 and 12 weeks after surgery or the last injection with the use of propensity score matching. Results: In 132 matched subjects who were treated with collagenase ( n = 66) or fasciectomy ( n = 66), the degree of residual contracture at follow-up for affected metacarpophalangeal joints was not significantly different (13 degrees versus 6 degrees; p = 0.095) and affected proximal interphalangeal joints had significantly worse residual contracture in the collagenase group compared with those in the fasciectomy group (25 degrees versus 15 degrees; p = 0.010). Collagenase subjects experienced fewer serious adverse events than did fasciectomy subjects and reported larger improvements in the Michigan Hand Outcomes Questionnaire subscores evaluating satisfaction with hand function, activities of daily living, and work performance. Conclusions: This propensity score–matched study showed that collagenase clostridium histolyticum was not significantly different from limited fasciectomy in reducing metacarpophalangeal joint contractures, whereas proximal interphalangeal joint contractures showed slightly better reduction following limited fasciectomy. Collagenase provided a more rapid recovery of hand function than did fasciectomy and was associated with fewer serious adverse events. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.